2020
DOI: 10.1101/2020.01.21.914663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel strategy for single-cell metabolic analysis highlights dynamic changes in immune subpopulations

Abstract: A complex interaction of anabolic and catabolic metabolism underpins the ability of leukocytes to mount an immune response. Their capacity to respond and adapt to changing environments by metabolic reprogramming is crucial to their effector function. However, current methods lack the ability to interrogate this network of metabolic pathways at the single cell level within a heterogeneous population. Here we present Met-Flow, a novel flow cytometry-based method that captures the metabolic state of immune cells … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…We made a selection of nutrient transporters and metabolic enzymes of core metabolic pathways based on previous studies, and of known relevance to mph function (Ahl et al, 2020;Covarrubias et al, 2020;Hartmann et al, 2021) (Figure 1A). Analysis of murine bone marrow-derived mphs (BMDMs) treated with inflammatory stimuli (LPS+IFNγ), to induce a classically activated 'M1' phenotype, demonstrated increased features of glycolysis and the pentose-phosphate pathway, as well as an altered tricarboxylic acid (TCA) cycle.…”
Section: In Vitro Differentiated Macrophages Acquire Divergent Metabo...mentioning
confidence: 99%
See 1 more Smart Citation
“…We made a selection of nutrient transporters and metabolic enzymes of core metabolic pathways based on previous studies, and of known relevance to mph function (Ahl et al, 2020;Covarrubias et al, 2020;Hartmann et al, 2021) (Figure 1A). Analysis of murine bone marrow-derived mphs (BMDMs) treated with inflammatory stimuli (LPS+IFNγ), to induce a classically activated 'M1' phenotype, demonstrated increased features of glycolysis and the pentose-phosphate pathway, as well as an altered tricarboxylic acid (TCA) cycle.…”
Section: In Vitro Differentiated Macrophages Acquire Divergent Metabo...mentioning
confidence: 99%
“…Metabolic flow or mass cytometry targeting nutrient transporters and enzymes has recently been pioneered as a highly promising alternative to analyze immune metabolism at the single-cell level (Ahl et al, 2020;Geeraerts et al, 2021;Hartmann et al, 2021). These methods for metabolic analysis have yet to define the tissue-specific metabolic states, or responses, of mphs.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the third group uses mass spectometry and mass-spectrometry imaging to measure the levels of different metabolites produced by EM pathways 10 . Very recently, CyTOF-based quantification of different metabolic enzymes was used in parallel to histology to correlate expression of metabolic enzymes with the microanatomical localization of mouse and human T cells [11][12][13] . Current methods need large numbers of highly purified cells 14 , and dedicated equipments, and thus cannot be applied to establish functional EM profiles of heterogenous and scarce living cell populations obtained from human samples or biopsies 15 (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the third group uses mass spectometry and mass-spectrometry imaging to measure the levels of different metabolites produced by EM pathways(Palmer et al, 2016). Very recently, CyTOF-based quantification of different metabolic enzymes was used in parallel to histology to correlate expression of metabolic enzymes with the microanatomical localization of mouse and human T cells(Ahl et al, 2020; Hartmann et al, 2020; Levine et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, a better understanding of their metabolic demands may provide valuable insights for their therapeutic targeting.NKT cells differ from their conventional CD4 + T cell counterparts in that NKT cells metabolise glucose through the pentose phosphate pathway(PPP) and tricarboxylic acid (TCA) cycle, as opposed to being converted to lactate via glycolysis[54]. In keeping with this, a recent study on the metabolic profile of T cells in PBMCs demonstrated that key metabolites for the TCA cycle and fatty acid oxidation were higher in NKT cells than conventional CD4 + T cells[55].Activation in iNKT cells is associated with enhanced glycolysis. However, activated iNKT cells are also characterized by increased mitochondrial capacity, further confirming that aerobic glycolysis and oxidative phosphorylation are not mutually exclusive processes [56].…”
mentioning
confidence: 99%